PETA PEMIKIRAN PENDIDIKAN ISLAM DI INDONESIA: Telaah Dikotomi Pendidikan - Taufik, Taufik (State Institute of Islamic Studies (IAIN) Palu, 2010)
The development of today’seducation in Indonesia cannot be separated from the influence of the ideas of western state and those of the Islamic state. The influence brings about the dichotomy of Islamic education and general education, and the various ideas on the purposes of education based on religion, politics, and area. Both the Islamic education institution and general education institution have their own objective of education. The infect is that there will be some intellectuals having no good morals. To minimize the dichotomy of education in Indonesia, there must be restoration of Islamic education system and public education.Kata Kunci: pendidikan Islam, pendidikan umum, dikotomi pendidikan